Seismic methods in mineral exploration and mine planning: A general overview of past and present case histories and a look into the future. - Malehmir, A.; Durrheim, R.; Bellefleur, G.; Urosevic, Milovan; Juhlin, C.; White, D.; Milkereit, B.; Campbell, Geoff (Society of Exploration Geophysics, 2012)
Due to high metal prices and increased difficulties in finding shallower deposits, the exploration for and exploitation of mineral resources is expected to move to greater depths. Consequently, seismic methods will become a more important tool to help unravel structures hosting mineral deposits at great depth for mine planning and exploration. These methods also can be used with varying degrees of success to directly target mineral deposits at depth. We review important contributions that have been made in developing these techniques for the mining industry with focus on four main regions: Australia, Europe, Canada, and South Africa. A wide range of case studies are covered, including some that are published in the special issue accompanying this article, from surface to borehole seismic methods, as well as petrophysical data and seismic modeling of mineral deposits. At present, high-resolution 2D surveys mostly are performed in mining areas, but there is a general increasing trend in the use of 3D seismic methods, especially in mature mining camps.